2011
DOI: 10.1039/c0cc04400h
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a two-dimensional halogen-bonded cocrystal at sub-monolayer coverage using synchrotron X-ray diffraction

Abstract: The formation of two-dimensional halogen-bonded layers of 4,4'-bipyridyl and 1,4-diiodotetrafluorobenzene was observed on a graphite surface at sub-monolayer coverage using synchrotron X-ray diffraction; the use of the diffraction technique enabled, for the first time, the measurement of I···N halogen bonding distances in a two-dimensional cocrystal and the identification of the halogen bonding interaction in the monolayer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 33 publications
3
33
0
Order By: Relevance
“…In the BPY/DITFB colayer structure (see figure 2b in ref (10)), the molecules form extended chains of alternating DITFB and BPY. There is evidence of a strong halogen bond between the iodine atoms of DITFB and the nitrogen atoms of BPY, as deduced from the internuclear separation (2.84 Å), which is shorter than the sum of the van der Waals radii of the species.…”
Section: Introductionmentioning
confidence: 99%
“…In the BPY/DITFB colayer structure (see figure 2b in ref (10)), the molecules form extended chains of alternating DITFB and BPY. There is evidence of a strong halogen bond between the iodine atoms of DITFB and the nitrogen atoms of BPY, as deduced from the internuclear separation (2.84 Å), which is shorter than the sum of the van der Waals radii of the species.…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with many sub-monolayer coverage physisorbed layers, which show melting points lowered by a greater degree relative to the bulk, typically by a factor of approximately 0.75. While some molecules do form solid monolayers close to, or indeed on rare occasions above [5,7,12], the bulk melting point even at sub-monolayer coverages, such layers are normally stabilized by strong intermolecular interactions like hydrogen bonds [5,12].…”
Section: Discussionmentioning
confidence: 99%
“…Molecules containing pyridine moieties are notable for their ability to act as ligands, allowing surface selfassembly via a range of non-covalent interactions such as hydrogen bonding [3,4], halogen bonding [5] and metal coordination [2]. In addition, these molecules have been shown to form ordered single-component monolayers, whose structure is guided by the formation of weak C-H � � � N hydrogen bonds [6,7].…”
Section: Introductionmentioning
confidence: 98%
“…The apparatus and procedures for the synchrotron X-ray [24,28], Neutron [9,36] and DSC [19,37] have been described elsewhere. The instrument used for the synchrotron experiment was I11 [38] at the Diamond Light Source, Didcot, UK.…”
Section: Methodsmentioning
confidence: 99%
“…In addition alkyl species with functional groups such as alcohols [15][16][17][18][19][20] and fatty acids [21][22][23] are also reported to form similar stable solid monolayers. Recently it has been found that the formation of very stable solid monolayers can be enhanced by a variety of non-covalent interactions within the monolayer, such as hydrogen bonding [24][25][26][27], halogen-halogen bonding [28,29], halogen bonding [28] even at temperatures significantly above the bulk melting point where the bulk adsorbate is liquid.…”
Section: Introductionmentioning
confidence: 99%